2020
DOI: 10.3126/njms.v5i1.36949
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: The prevalence of anxiety and depression among patients with COPD is significantly higher than the general population; there are serious barriers to the recognition and treatment of these co-morbid conditions. The study aimed to identify the anxiety and depression among patients with COPD. Methods: A cross sectional study design was adopted and consecutive sampling technique was used to collect 131 samples. A structured interview schedule of Beck Depression Inventory and Beck Anxiety Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Of the participants, 34% showed signs of moderate and 8.7% severe depression. Acharya et al, in their study with patients who had a chronic pulmonary obstructive disease, demonstrated that 23.7% had moderate, 10.7% had severe, and 5.3% had very severe depression (19,20). Abu Ameerh and Hamad, in their study with diabetes patients, demonstrated that 30.3% had moderate, 14.2% had severe, and 3.2% had very severe depression (21).…”
Section: Discussionmentioning
confidence: 97%
“…Of the participants, 34% showed signs of moderate and 8.7% severe depression. Acharya et al, in their study with patients who had a chronic pulmonary obstructive disease, demonstrated that 23.7% had moderate, 10.7% had severe, and 5.3% had very severe depression (19,20). Abu Ameerh and Hamad, in their study with diabetes patients, demonstrated that 30.3% had moderate, 14.2% had severe, and 3.2% had very severe depression (21).…”
Section: Discussionmentioning
confidence: 97%